Diagnosis of GM-1 gangliodosis in Cuba - Caridad Menéndez Saínz; Sergio González García; Claudina Zaldívar Muñoz; Alina González-Quevedo Monteagudo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2007)
Background: GM-1 gangliosidosis is included in the group of lysosomal diseases and is characterized by a deficiency of the enzyme b-galactosidase, which as a consequence produces accumulation of GM1 ganglioside in nervous cells and galactosil oligosaccharides and products of keratan sulfate degradation in other tissues. Clinically this disease presents with an early psychomotor impairment, macular cherry red spots, facial dysmorphia, bone deformities and hepatosplenomegaly. It has a hereditary autosomic-recessive pattern. Objective: To determine of β-galactosidase acid activity in patients with suspicion of GM-1 gangliosidosis. Methods: From 1986 to 2006, 1851 patients have been received in our laboratory from all the country, of which 851 had the diagnostic impression of GM-1 gangliosidosis. In samples from patients, parents and controls, the activity of leukocyte b-galactosidase was determined by a fluorimetric technique (metilumbelliferil derivatives) and leukocyte protein level was determined according to Lowry's method. Results and conclusions: The diagnosis of GM-1 gangliosidosis was attained in 11 patients, and the enzymatic activity was three times lower in patients with respect to their parents and five times lower with respect to controls. The enzymatic activity was not related with gender or age.